Application of Pacta Sunt Servanda Principle in District Court Decision - Aisyah, Siti; Dianita, Andi Citra; Ismiyanti, Ismiyanti; Hasmiati, Hasmiati; Salmi, Salmi (PT. Anagata Sembagi Education, 2025)
The Pacta Sunt Servanda principle is one of the fundamental principles in the law of agreements which emphasizes that every agreement made legally binds the parties like a law. This research aims to analyze the application of the Pacta Sunt Servanda principle in the Indonesian legal system, especially in court decisions, and identify exceptions to the principle. The research method used is a normative juridical approach by analyzing laws and regulations, court decisions, and relevant legal literature. The results showed that this principle is regulated in Article 1338 paragraph (1) of the Civil Code, which emphasizes that a valid agreement must be carried out in good faith. However, there are exceptions in certain circumstances, such as force majeure (Article 1245 of the Civil Code) and the principle of justice in Article 1339 of the Civil Code. Case studies of court decisions show that although the principle of Pacta Sunt Servanda is generally applied consistently, there are variations in its interpretation, especially in cases involving public interest and consumer protection. The implication of this research is the need for caution in drafting contracts so that they do not only fulfill the elements of legality, but also consider aspects of justice and propriety. Thus, this research provides insights for academics, legal practitioners, and policy makers in understanding the dynamics of the application of Pacta Sunt Servanda in Indonesian treaty law.